(untitled) (Comunicação & Inovação, 2024)
This article brings together elaborations that seek to understand how communication, from the perspective of the confluence of knowledge, can be affected by decoloniality, an essential perspective in the Latin American context. Imagining such a theoretical, methodological, and political horizon seems crucial for the historically and socially referenced construction of knowledge in the communication and journalistic fields, especially in countries repressed by the coloniality of power and knowledge. As a result, the article presents approximations between these understandings and the notion of communicative citizenship.